Possible mechanical causes of scaffold thrombosis: Insights from case reports with intracoronary imaging - Yohei Sotomi (2018)
© Europa Digital & Publishing 2017. All rights reserved. The advent of intracoronary stents has greatly increased the safety and applicability of percutaneous coronary interventions. One of the drawbacks of drug-eluting stents (DES) is the increased risk of late and very late stent thrombosis (ST). It was anticipated that the risks of ST after DES implantation would be solved with the advent of fully biodegradable scaffolds, which offer the possibility of transient scaffolding of the vessel to prevent acute vessel closure and recoil while also transiently eluting an antiproliferative drug to counteract constrictive remodelling and excessive neointimal hyperplasia. In spite of the enthusiasm for the concept of bioresorbable scaffolds, current clinical data on the Absorb bioresorbable vascular scaffold (BVS) have generated concerns about scaffold thrombosis (ScT) in both the early and late phases. However, the causes of ScT in both the early and late phases have yet to be fully elucidated. This article seeks to provide insights into the possible mechanical causes of ScT in the early and late phases with data stemming from intracoronary imaging (intravascular ultrasound and optical coherence tomography) of the currently published ScT cases following the implantation of BVS and reviews the practical recommendations for implantation of the BVS made by a group of experts.